Medicalization focusing on the indiscriminate use of methylphenidate: An integrative review (Research, Society and Development, 2022)
The impacts that the phenomenon of medicalization has been causing are delimited by a fine line that divides the necessary medication and the medicalization of life, this reality is perceived in different spaces. In this scenario, methylphenidate is the most explored, being the most consumed psychotropic in the world, its pharmacological characteristics have historically created a concern about its potential as a drug of abuse. The objective sought was to identify the harm caused by medicalization, in order to specifically focus on the indiscriminate use of methylphenidate within this context. The methodology consists of an integrative review, in which the platforms: SciELO, Medline, Lilacs and the PubMed library were used to search for data. That culminated in the broad assessment of the theme in different contrasts around the world, going beyond the medical system and covering the cultural sphere of self-efficacy, which prioritizes performance over physical and mental health, finding no other way to do it than by potentiating it. chemistry of the results.